Plasma-resistant fluororubber and method for producing the same

CN122978619APending Publication Date: 2026-10-27DONGGUAN TEKTRONIX SEALING TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611160854.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-03
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0003]专利文献CN121249076A 采用 h-BN 和贵金属负载的氧化铈均匀共混作为填料,成本高,而且等离子长期轰击下,存在贵金属颗粒脱落的风险,而且填料改性工艺苛刻,需要二氟化氙密闭高压反应釜,二氟化氙属于剧毒、强腐蚀高危氟化试剂,高压反应对设备密封、防爆要求极高

Benefits of technology

[0022]优选地,步骤S3中采用两段硫化,一段模压硫化:在模具温度160-170℃,压力 10-15MPa,保压 10-15min 定型交联;二段真空后硫化:升温至220-230℃,真空<10Pa,保温4-6 h,以便充分硫化,完善交联网络,持久改善压缩永久变形,同时脱除小分子挥发物,满足半导体低释气要求,而且可释放成型内应力。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application discloses a kind of plasma-resistant fluorine rubber and preparation method thereof, belong to the field of rubber material.The plasma-resistant fluorine rubber of the application includes the following raw material components by weight fraction: perfluoroether rubber green rubber 100 parts, SiC nanowire 5-15 parts, SiC nanoparticle 5-15 parts, vulcanizing agent 1-5 parts, crosslinking agent 1-3 parts, polytetrafluoroethylene micro powder 3-10 parts, silane coupling agent 0.5-2 parts;The perfluoroether rubber material of the application has good high-temperature resistance, can resist oxygen, fluorine plasma erosion simultaneously, the metal ion precipitation amount is low, and simultaneously has good mechanical properties and low compression permanent deformation, and can be used for semiconductor plasma cavity sealing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of rubber materials, and specifically relates to a plasma-resistant fluororubber and its preparation method. Background Technology

[0002] As integrated circuit manufacturing processes continue to iterate towards advanced 7nm and 14nm processes, the cavities of core equipment such as etching, ALD, and CVD are constantly exposed to high-density plasma environments of SF6, CF4, and O2. The cavity sealing rings must simultaneously withstand high-energy ion sputtering, fluorine / oxygen free radical chemical corrosion, and high-low temperature cyclic alternating loads, while strictly limiting the precipitation of metal ions, small organic molecules, and solid particles to avoid wafer defects and yield reduction.

[0003] Patent document CN121249076A uses a uniform blend of h-BN and precious metal-loaded cerium oxide as filler, which is costly and poses a risk of precious metal particles falling off under long-term plasma bombardment. Moreover, the filler modification process is demanding and requires a closed high-pressure reactor containing xenon difluoride. Xenon difluoride is a highly toxic, corrosive, and hazardous fluorinating agent, and the high-pressure reaction places extremely high demands on the equipment's sealing and explosion-proof requirements.

[0004] Patent document CN116218104A uses graphene oxide filler, but carbon filler is easily ablated under oxygen plasma, producing carbon particles, making it unsuitable for advanced processes. Therefore, improvements to the existing technology are still needed. Summary of the Invention

[0005] To address the technical deficiencies in the existing technologies, this invention provides a plasma-resistant fluororubber based on SiC filler. By combining SiC nanowires and nanoparticles with optimized formulation and process, a thermally conductive barrier network is formed, reducing the plasma erosion rate and resulting in low metal precipitation. It is suitable for various plasmas, especially fluorine / oxygen plasmas, and also improves material toughness and reduces compression set, making it suitable for sealing semiconductor ion chambers.

[0006] To achieve the above objectives, the present invention is implemented through the following technical solution: In a first aspect, the present invention provides a plasma-resistant fluororubber, comprising, by weight, the following raw material components: 100 parts of perfluoroether rubber raw rubber, 5-15 parts of SiC nanowires, 5-15 parts of SiC nanoparticles, 1-5 parts of vulcanizing agent, 1-3 parts of crosslinking agent, 3-10 parts of polytetrafluoroethylene (PTFE) micropowder, and 0.5-2 parts of silane coupling agent; wherein the perfluoroether rubber raw rubber is a tetrafluoroethylene-perfluoroalkyl vinyl ether-halogen vulcanizing monomer raw rubber.

[0007] The plasma-resistant fluororubber of this invention is based on perfluoroether rubber containing halogenated vulcanizing monomers, and uses SiC nanowires and SiC nanoparticles modified with silane coupling agents as inorganic fillers, combined with polytetrafluoroethylene organic fillers, vulcanizing agents and crosslinking agents. The resulting perfluoroether rubber material is resistant to high temperature and plasma etching, has low metal ion precipitation, and also has good mechanical properties and low compression set, making it suitable for semiconductor sealing.

[0008] Furthermore, the perfluoroalkyl vinyl ether is a perfluoromethyl vinyl ether; the fluorine content of the perfluoroether rubber raw rubber is 70-75%, the Mooney viscosity is 70-100 MU under ML1+10 and 121℃ conditions, and the vulcanizing monomer is a halogen vulcanizing monomer.

[0009] Further, the SiC nanowires have a diameter of 20 nm to 50 nm and an aspect ratio of 20 to 30; the SiC nanoparticles have a diameter of 50 to 200 nm; and the weight ratio of SiC nanowires to SiC nanoparticles is 0.3 to 3:1. Preferably, the weight ratio of SiC nanowires to SiC nanoparticles is 1 to 3:1. More preferably, the weight ratio of SiC nanowires to SiC nanoparticles is 3:1.

[0010] Further, the vulcanizing agent is at least one selected from dicumyl peroxide and 2,5-dimethyl-2,5-di-tert-butylperoxyhexane. In some preferred embodiments, the vulcanizing agent is 2,5-dimethyl-2,5-di-tert-butylperoxyhexane.

[0011] Furthermore, the crosslinking agent is triallyl isocyanurate.

[0012] Furthermore, the silane coupling agent is at least one of vinyltrimethoxysilane and vinyltriethoxysilane.

[0013] Furthermore, the particle size of the polytetrafluoroethylene is 10-60 μm.

[0014] A second aspect of the present invention also provides a method for preparing the above-mentioned plasma-resistant fluororubber, comprising the following steps: S1 filler modification; SiC nanoparticles were added to an organic solvent to prepare a solution with a concentration of 10-25 wt%. A portion of silane coupling agent was added, and the mixture was ball-milled, filtered, and dried to obtain silane-modified SiC nanoparticles. SiC nanowires were immersed in toluene, and the remaining silane coupling agent and the silane-modified SiC nanoparticles were added. The mixture was refluxed at 80-120°C and dried to obtain the modified filler. S2 blending; The perfluoroether rubber raw rubber, the modified filler, polytetrafluoroethylene micro powder, and vulcanizing agent are added to a mixer, mixed at 40-75℃, and then degassed under vacuum to obtain the masterbatch. Then, the masterbatch is repeatedly turned and thin-passed on the open mill, formed into triangular bags, and mixed evenly before being sheeted and left at room temperature for 12-18 hours. S3 vulcanization molding; Vulcanization and setting are carried out at 160-230℃.

[0015] In the preparation method of the present invention, in step S1, SiC nanoparticles are first ball-milled and modified, and then refluxed together with SiC nanowires for modification, so as to retain the aspect ratio of SiC fibers as much as possible, while SiC nanoparticles and nanowires can be fully dispersed.

[0016] Preferably, in step S1, the organic solvent includes at least one of toluene, ethanol, tetrahydrofuran, and ethyl acetate.

[0017] Preferably, in step S1, the ball milling speed is 100-300 rpm and the ball milling time is 1-3 h.

[0018] In the preparation method of the present invention, in step S2, each raw material is first added gradually in a mixer to rapidly disperse the filler, and then refined in a two-roll mill. The combination of the two processes can fully disperse the filler, and the SiC nanowires are oriented along the shear direction. The SiC nanoparticles are dispersed and fill the gaps between the nanowires, forming a through-type thermally conductive network, which greatly improves the directional thermal conductivity. The addition of polytetrafluoroethylene can improve lubricity and facilitate the orientation of SiC nanowires under shear conditions, forming a three-dimensional network.

[0019] Preferably, in step S2, the perfluoroether rubber raw rubber is first added to a Banbury mixer and initially mixed for 3-5 minutes at a temperature of 55-65℃ and a rotation speed of 20-30 rpm. Then, the modified filler and polytetrafluoroethylene micro powder are added, and the mixture is mixed for 5-10 minutes at a temperature of 65-75℃ and a rotation speed of 40-60 rpm. Next, the vulcanizing agent and crosslinking agent are added, and the mixture is further mixed for 3-5 minutes at a temperature of 40-50℃ and a rotation speed of 10-20 rpm. After vacuum degassing, the mixture is discharged to obtain the masterbatch. The raw rubber is first added and dispersed at a low speed, then the rotation speed and temperature are increased, the filler is added and dispersed rapidly, and finally the vulcanizing agent is added and the mixture is blended again with each agent. This facilitates the rapid dispersion of the filler, allowing SiC nanowires and SiC nanoparticles to synergistically form a rigid filler physical network.

[0020] Preferably, in step S2, the turning speed of the open mill is 10-20 m / min, and the roll gap is 0.1-1.0 mm. More preferably, the turning speed is 10-20 m / min, and the roll gap is 0.3-0.8 mm.

[0021] In the preparation method of the present invention, in step S3, the material is cured at an appropriate temperature to fully vulcanize and form an interpenetrating cross-linked network system with high interfacial bonding strength. The rigid filler physical network is fixed, which can limit the long slip of rubber molecular chains, thereby improving the material's compression set. Moreover, the material has excellent thermal conductivity and mechanical properties.

[0022] Preferably, step S3 employs a two-stage vulcanization process: a first-stage compression vulcanization, where the mold temperature is 160-170℃, the pressure is 10-15MPa, and the pressure is held for 10-15 minutes to achieve cross-linking; and a second-stage vacuum post-vulcanization, where the temperature is raised to 220-230℃, the vacuum is <10Pa, and the temperature is held for 4-6 hours to ensure sufficient vulcanization, improve the cross-linking network, and permanently improve compression set. This process also removes small molecule volatiles, meets the low gas release requirements of semiconductors, and releases the internal stress of the molding process.

[0023] Compared with existing technologies, this invention uses perfluoroether rubber containing halogenated vulcanizing monomers as the main body, combined with silane coupling agent-modified SiC nanowires and SiC nanoparticles as inorganic fillers, and polytetrafluoroethylene organic fillers, vulcanizing agents, and crosslinking agents. Through specific filler modification, blending and vulcanization processes, an interwoven and continuous three-dimensional thermally conductive network is formed. The resulting perfluoroether rubber material has good high-temperature resistance, can resist oxygen and fluorine plasma corrosion simultaneously, has a low outgassing rate, and has good mechanical properties and low compression set, making it suitable for sealing semiconductor plasma chambers. Detailed Implementation

[0024] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. The specific embodiments described herein are for illustrative purposes only and are not intended to limit the invention.

[0025] The raw materials and reagents used in the following examples (unless otherwise specified) were all commercially available; the techniques and methods used (unless otherwise specified) were all conventional means in the art.

[0026] Raw material description: Perfluoroether rubber raw material: Sowell PFR 95HT.

[0027] Example 1 A plasma-resistant fluororubber, by weight, comprises the following raw material components: 100g of perfluoroether rubber raw rubber, 15g of SiC nanowires, 5g of SiC nanoparticles, 2.5g of vulcanizing agent, 2g of crosslinking agent, 5g of polytetrafluoroethylene (PTFE) micro powder, and 1.5g of silane coupling agent.

[0028] The perfluoroether rubber raw material is Sowell PFR 95HT, with a fluorine content of 75% and a Mooney viscosity of 75 MU at ML1+10 and 121°C.

[0029] SiC nanowires: diameter 20-50 nm, aspect ratio 20-30; SiC nanoparticles: diameter 50-200nm; Vulcanizing agent: 2,5-dimethyl-2,5-di-tert-butylperoxyhexane, purity >90%; Crosslinking agent: Triallyl isocyanurate, purity >90%; Silane coupling agent: Vinyltrimethoxysilane; Polytetrafluoroethylene micro powder: particle size 10-60μm.

[0030] Its preparation method includes the following steps: S1 filler modification; SiC nanoparticles were added to anhydrous ethanol to prepare a 20% solution. 1g of silane coupling agent was added, and the mixture was ball-milled at 200rpm for 2h to mix. The mixture was then filtered and dried to obtain silane-modified SiC nanoparticles. SiC nanowires were immersed in 2L of toluene, and 0.5g of silane coupling agent and silane-modified SiC nanoparticles were added. The mixture was then refluxed at 100℃ for 10 h under nitrogen protection, washed three times with toluene, and dried under vacuum at 120℃.

[0031] S2 blending.

[0032] Preheat the internal mixer to 60°C, add perfluoroether rubber raw rubber first, mix at 25 rpm for 3 minutes, then add the filler modified in step S1 and polytetrafluoroethylene micro powder, heat to 75°C, continue mixing at 50 rpm for 8 minutes, then cool to 45°C, add vulcanizing agent and crosslinking agent, continue mixing at 15 rpm for 5 minutes, then degas under vacuum for 10 minutes, and discharge to obtain masterbatch.

[0033] The open mill was set to a turning speed of 17.1 m / min and a roll gap of 0.6 mm. The obtained masterbatch was turned on the open mill, passed through multiple thin passes, formed into triangular bundles, and mixed evenly. The mixture was then sheeted and left at room temperature for 16 hours to cure in order to eliminate the internal stress of the blend.

[0034] S3 vulcanization molding.

[0035] Two-stage vulcanization is adopted. The first stage is compression vulcanization: the mold temperature is 165℃, the pressure is 12MPa, and the pressure is held for 12min to set the crosslinking. The second stage is vacuum post-vulcanization: the temperature is raised to 260℃, the vacuum degree is adjusted to <10Pa, and the temperature is held for 5h.

[0036] Example 2 The difference from Example 1 is that the amount of SiC nanowires and SiC nanoparticles is different, specifically 10g of SiC nanowires and 10g of SiC nanoparticles; all other aspects are the same.

[0037] Example 3 The difference from Example 1 is that the amount of SiC nanowires and SiC nanoparticles is different, specifically 5g of SiC nanowires and 15g of SiC nanoparticles; all other aspects are the same.

[0038] Example 4 The difference from Example 1 is that the amount of polytetrafluoroethylene (PTFE) micro powder is different, specifically 3g of PTFE micro powder, while the rest are the same.

[0039] Example 5 The difference from Example 1 is that the amount of polytetrafluoroethylene (PTFE) micro powder is different, specifically 10g of PTFE micro powder, while the rest are the same.

[0040] Comparative Example 1 The difference from Example 1 is that it does not contain SiC nanowires, but all other aspects are the same.

[0041] Comparative Example 2 The only difference from Example 1 is that it does not contain SiC nanoparticles; all other aspects are the same.

[0042] Comparative Example 3 The only difference from Example 1 is that it does not contain polytetrafluoroethylene micropowder; all other aspects are the same.

[0043] Comparative Example 4 The difference from Example 1 is that in step S1, SiC nanoparticles and SiC nanowires are directly grafted using a silane coupling agent mixed and refluxed, as detailed below: S1 packing modification pretreatment; SiC nanowires, SiC nanoparticles, and silane coupling agent were immersed in 2L of toluene, refluxed at 100 °C for 10 h under nitrogen protection, then washed three times with toluene and dried under vacuum at 120 °C.

[0044] Comparative Example 5 The difference from Example 1 is that in step S2, the rotation speed and temperature in the internal mixer are not changed, and all raw materials are mixed together, as follows: Preheat the internal mixer to 60°C, add perfluoroether rubber raw rubber, filler modified in step S1, polytetrafluoroethylene micro powder, vulcanizing agent and crosslinking agent, mix at 25 rpm for 17 min, then degas under vacuum for 10 min, and discharge to obtain masterbatch.

[0045] The open mill was set to a turning speed of 17.1 m / min and a roll gap of 0.6 mm. The obtained masterbatch was turned on the open mill, passed through multiple thin passes, formed into triangular bundles, and mixed evenly. The mixture was then sheeted and left at room temperature for 16 hours to cure in order to eliminate the internal stress of the blend.

[0046] Comparative Example 6 The difference from Example 1 is that in step S2, only the open mill is used for mixing, as detailed below: S2 blending; Set the open mill turning speed to 17 rpm and the roller gap to 0.6 mm. First, add the perfluoroether rubber raw rubber, pass it through the rollers 3 times, and form 5 triangular clumps. Then, wrap the raw rubber around the front roller, forming a pile of rubber above the gap between the two rollers. Slowly pour the filler modified in step S1, polytetrafluoroethylene micro powder, into the rubber compound piled on the rollers, pass it through the rollers multiple times, and form 5 triangular clumps. Then add the vulcanizing agent and crosslinking agent, pass it through the rollers multiple times, and form 5 triangular clumps. After mixing evenly, sheet out and let it mature at room temperature for 16 hours to eliminate the internal stress of the blend.

[0047] Performance testing: 1) Weight reduction rate of plasma etching Testing apparatus: Surface wave plasma etching apparatus; Cooling water set temperature: 120℃; Sample type: Coarse / fine 3.53 mm. 30. Rope-like.

[0048] Gas type, output power, and exposure time: see Table 1-2.

[0049] Mass loss rate: M loss = (m1- m2) / m1× 100%, where m1 is the mass before etching and m2 is the mass after etching.

[0050] 2) Gas release rate The TGA test involved heating the temperature to 350°C at the same rate, holding it at that temperature for 42.5 minutes, and then measuring the change in mass.

[0051] 3) Compression permanent deformation The material was subjected to a 72-hour compression set test at 204°C according to ASTM D395-03 Method B.

[0052] 4) Thermal conductivity test According to ASTM E1461 standard, the thermal conductivity of materials perpendicular to the plasma incident direction was tested using the laser flash method at a test temperature of 25°C.

[0053] 5) Shore A hardness According to ASTM D2240-05 standard, the hardness of the material was tested using a Shore A hardness tester, and the average value was taken from 5 test points.

[0054] 6) Tensile strength, MPa; Elongation at break, % According to ASTM D412-06a, the tensile strength of the material was tested using a universal testing machine at a tensile speed of 500 mm / min, and 5 samples were tested for each test and the average value was taken.

[0055] The performance test results of each embodiment and comparative example are shown in Table 1 and Table 2.

[0056] Table 1 Performance test results of the embodiment

[0057] Table 2 Comparative Performance Test Results

[0058] The results above show that: 1) The fluororubber of the present invention has a compression set of ≤10% at 72h / 204℃ and a thermal conductivity of >3.5W / (m·K). It performs well in O2, CF4 and H2 plasma etching, especially in O2 and CF4 plasma etching, where the weight loss is less than 0.6%, and it has good tensile strength and hardness, with an elongation at break of up to 223%.

[0059] 2) Comparing Examples 1-3, it was found that the performance was superior in all aspects when the ratio of SiC nanowires to SiC nanoparticles was 3:1. Further combining the results of Examples 4 and 5, it can be seen that SiC nanowires and SiC nanoparticles are the main factors affecting performance, followed by PTFE. However, Examples 4 and 5 show that the performance is best when the PTFE dosage is 5g. Reducing the dosage affects network formation, leading to decreased heat dissipation performance, toughness, and compression set performance. Increasing the dosage, since PTFE is a poor thermal conductor, also affects the formation of the heat dissipation network of the inorganic filler, thus affecting thermal conductivity.

[0060] 3) In Comparative Example 1, there is no SiC nanowire, only SiC nanoparticles, which makes it difficult to form a three-dimensional filler network, resulting in a significant decrease in various properties. Similarly, in Comparative Example 2, there is no SiC nanoparticle, only SiC nanowires. The lack of connection between the nanowires also leads to a decrease in thermal conductivity and plasma etching resistance.

[0061] 4) In Comparative Example 3, the absence of PTFF affects the structural orientation during the shearing process, thereby affecting the formation of the filler network and significantly reducing the performance in all aspects.

[0062] 5) In Comparative Example 4, SiC nanowires and nanoparticles were refluxed together. The step of pre-modification and dispersion treatment of nanoparticles was missing, which could not effectively break up the agglomeration between nanoparticles. As a result, the SiC nanowires and nanoparticles could not be well dispersed to form a three-dimensional filler network, leading to a significant decrease in various properties.

[0063] 6) In Comparative Examples 5 and 6, changing the blending method makes it difficult to disperse the mixture well and form an effective three-dimensional network, resulting in a sharp decline in performance in all aspects.

[0064] In summary, this invention utilizes perfluoroether rubber containing halogenated vulcanizing monomers as the main body, combined with silane coupling agent-modified SiC nanowires and SiC nanoparticles as inorganic fillers, and polytetrafluoroethylene organic fillers, vulcanizing agents, and crosslinking agents. Through specific modification and vulcanization processes, an interwoven and continuous three-dimensional thermally conductive network is formed. The resulting perfluoroether rubber material exhibits excellent high-temperature resistance, can simultaneously resist oxygen and fluorine plasma corrosion, has low metal ion release, and also possesses good mechanical properties and low compression set, making it suitable for sealing semiconductor plasma cavities.

[0065] The embodiments of the present invention have been described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions, and variations can be made to these embodiments without departing from the principles and spirit of the present invention, and these variations still fall within the protection scope of the present invention.

Claims

1. A plasma-resistant fluororubber, characterized in that, By weight, it includes the following raw material components: 100 parts of perfluoroether rubber raw material 5-15 parts of SiC nanowires 5-15 parts of SiC nanoparticles 1-5 parts of vulcanizing agent 1-3 parts of crosslinking agent 3-10 parts of polytetrafluoroethylene micro powder 0.5-2 parts of silane coupling agent; The perfluoroether rubber raw rubber is a tetrafluoroethylene-perfluoroalkyl vinyl ether-halogen vulcanized monomer raw rubber.

2. The plasma-resistant fluororubber according to claim 1, characterized in that, The perfluoroether rubber raw rubber has a fluorine content of 70-75 wt% and a Mooney viscosity of 70-100 MU at ML1+10 and 121°C; the perfluoroalkyl vinyl ether is a perfluoromethyl vinyl ether.

3. The plasma-resistant fluororubber according to claim 1, characterized in that, The SiC nanowires have a diameter of 20-50 nm and an aspect ratio of 20-30. The SiC nanoparticles have a diameter of 50-200 nm. The weight ratio of SiC nanowires to SiC nanoparticles is 0.3 to 3:

1.

4. The plasma-resistant fluororubber according to claim 1, characterized in that, The vulcanizing agent is at least one of dicumyl peroxide and 2,5-dimethyl-2,5-ditert-butylperoxyhexane; The crosslinking agent is triallyl isocyanurate.

5. The plasma-resistant fluororubber according to claim 1, characterized in that, The silane coupling agent is at least one of vinyltrimethoxysilane and vinyltriethoxysilane; and / or, the polytetrafluoroethylene particle size is 10-60 μm.

6. The method for preparing plasma-resistant fluororubber according to any one of claims 1-5, characterized in that, Includes the following steps: S1 filler modification; SiC nanoparticles were added to an organic solvent to prepare a solution with a concentration of 10-25 wt%. A portion of silane coupling agent was added, and the mixture was ball-milled, filtered, and dried to obtain silane-modified SiC nanoparticles. SiC nanowires were immersed in toluene, and the remaining silane coupling agent and the silane-modified SiC nanoparticles were added. The mixture was refluxed at 80-120°C and dried to obtain the modified filler. S2 blending; The perfluoroether rubber raw rubber, the modified filler, polytetrafluoroethylene micro powder, and vulcanizing agent are added to a mixer, mixed at 40-75℃, and then degassed under vacuum to obtain the masterbatch. Then, the masterbatch is repeatedly turned and thin-passed on the open mill, formed into triangular bags, and mixed evenly before being sheeted and left at room temperature for 12-18 hours. S3 vulcanization molding; Vulcanization and setting are carried out at 160-230℃.

7. The preparation method according to claim 6, characterized in that, In step S1, the organic solvent includes at least one of toluene, ethanol, tetrahydrofuran, and ethyl acetate; and / or, the ball milling speed is 100-300 rpm and the ball milling time is 1-3 h.

8. The preparation method according to claim 6, characterized in that, In step S2, the perfluoroether rubber raw rubber is first added to a mixer and initially mixed for 3-5 minutes at a temperature of 55-65℃ and a speed of 20-30 rpm. Then, the modified filler and polytetrafluoroethylene powder are added and mixed for 5-10 minutes at a temperature of 65-75℃ and a speed of 40-60 rpm. Next, the vulcanizing agent and crosslinking agent are added and mixed for another 3-5 minutes at a temperature of 40-50℃ and a speed of 10-20 rpm. After vacuum degassing, the material is discharged to obtain the masterbatch.

9. The preparation method according to claim 6, characterized in that, In step S2, the turning speed of the open mill is 10-20 m / min, and the roller gap is 0.1-1.0 mm.

10. The preparation method according to claim 6, characterized in that, In step S3, a two-stage vulcanization process is adopted. The first stage is compression vulcanization: the mold temperature is 160-170℃, the pressure is 10-15MPa, and the pressure is held for 10-15min to set the crosslinking. The second stage is vacuum post-vulcanization: the temperature is raised to 220-230℃, the vacuum is <10Pa, and the temperature is held for 4-6h.

Citation Information

Patent Citations

  • Preparation method of plasma-resistant graphene-based fluororubber sealing ring for semiconductor

    CN116218104A

  • Plasma-erosion-resistant fluororubber composite sealing material and preparation method thereof

    CN121249076A